An overview of and prospects for research on energy savings in wheel loaders - Fei, Xiaotao; Han, Yunwu; Wong, Shaw Voon (Universitas Muhammadiyah Magelang, 2023)
Wheel loaders consume a large amount of energy, and research on energy savings in wheel loaders has been carried out for decades. This paper introduces several types of wheel loaders and compares their structures. The research progress of the energy savings of three different forms of wheel loaders is reviewed, including a diesel engine wheel loader, a hybrid wheel loader, and an electric wheel loader. In particular, the energy-saving control methods of an electric wheel loader in the working cycle are analyzed, as construction machinery electrification is an emerging trend. Based on the analysis of the driving features and the working process of a wheel loader, energy-saving control methods are introduced including the resistance reduction method, optimized control strategies, intelligent control, and unmanned WL research. Comparing various energy-saving research methods and the advantages of electric wheel loaders, the pure electric wheel loaders are advised to be researched at present and in the future. Controlling the torque distribution of the front and rear motors of electric wheel loaders and assistant drive control are proposed to be significant research prospects for energy savings in wheel loaders usage.